FLORA OF SINGAPORE PRECURSORS, 2. A NEW SPECIES AND TWO NEW COMBINATIONS IN PSYDRAX (RUBIACEAE: VANGUERIEAE) FOR WEST MALESIA - Meng, Wong Khoon; Mahyuni, Ridha (REINWARDTIA, 2018)
WONG, K. M. & MAHYUNI, R. 2018. Flora of Singapore Precursors, 2. A new species and two new combinations in Psydrax (Rubiaceae: Vanguerieae) for West Malesia. Reinwardtia 17(1): 77â84. â Studies in Psydrax Gaertn. for the Flora of Singapore and the Malesian floristic region have revealed that three taxa required the description of a new species and two new combinations. Psydrax undulatifolius K.M.Wong & Mahyuni is newly described as a species thus far recorded only for the Malay Peninsula, whereas Psydrax approximatus (Korth.) Mahyuni & K.M.Wong and Psydrax lucidulus (Miq.) Mahyuni & K.M.Wong are newly combined from Canthium approximatum Korth. and Vangueria lucidula Miq., both distributed in Sumatra, the Malay Peninsula and Borneo.